Platform Fandom: Weverse and the Technological Domestication of Fan Community - Grant Bollmer; Bethany Tillerson (Social Media + Society)
This article is a critical examination of the social media platform Weverse and its associated e-commerce platform Weverse Shop, platforms developed and operated by the Korean entertainment conglomerate Hybe Corporation. Hybe, perhaps best known for being the corporation that manages the K-pop group BTS, uses Weverse to promote and control economic and affective bonds between popular performers and audiences. This article argues that Weverse represents a type of platform that negotiates other models emerging from American and Chinese contexts, advancing Korean corporate interests through the harnessing of integrated fan activities. The use of platform technologies to administer the relations between commodified musical products, stars, and fans represents the emergence of what we term platform fandom . Platform fandom, we argue, is a corporatized technical relation designed to foster affective attachments between fans and stars, negotiating global audiences in which fan communities lose geographic specificity and, consequently, an ability to cohere through the negotiation of inclusion and exclusion of members. This article uses Weverse as a case to examine the intersection of globalized cultural production and entertainment, problems of global fandoms, and the use of social media platforms to manage and mitigate against the seeming risks fans provide for both corporate idols and corporate investments in cultural products.